(untitled) (Philologia, 2021)
This paper is motivated by the studies of –ed adjectives (Hirtle 1970, Hudson 1975, Beard 1976) and gerunds (Borer 1990, Blevins 2005, Vujić 2006) in English. I base my study on the concept often advocated in modern morphological studies that gerunds and “–ed formations” are seen as dual representations, mixed category structures or dual lexical categories (Yoon 2005). In other words it is a well-known fact that, occasionally, administering a certain inflectional suffix may lead to a change in a part of speech category (class) of the base or Head (Yoon 2005). I use this fact as a starting point and continue with providing the arguments which support a hypothesis that the increasing number of similar dual category formations in the lexicon of modern English, allow for a revision of the position of inflection in relevance to derivation and WF in general. My point is that these two morphological mechanisms (inflection and derivation) in modern WF practice in English do not oppose each other. Rather, the limited and regulated scope of inflection is used to complement the imperfections and deficiencies of WF processes. Such a notion is additionally supported by the fact that both native and non-native speakers of English are familiar with grammatical, semantic and lexical features of inflectional affixes. Majority of speakers, in their mental lexicon, successfully interpret information added to the root or stem by the inflectional affixes. As a result, there are numerous new formations and neological formations showing dual nature in their internal and external properties (external distribution of one part-of-speech and internal syntax of another) (Lapointe 1999).